Antitumour benzothiazoles. Part 32: DNA adducts and double strand breaks correlate with activity; synthesis of 5F203 hydrogels for local delivery. Issue 21 (1st November 2015) - Stone, Erica L.; Citossi, Francesca; Singh, Rajinder; Kaur, Balvinder; Gaskell, Margaret; Farmer, Peter B.; Monks, Anne; Hose, Curtis; Stevens, Malcolm F.G.; Leong, Chee-Onn; Stocks, Michael; Kellam, Barrie; et al.
Graphical abstract: Abstract: Potent, selective antitumour AhR ligands 5F 203 and GW 610 are bioactivated by CYPs 1A1 and 2W1. Herein we reason that DNA adducts' generation resulting in lethal DNA double strand breaks (DSBs) underlies benzothiazoles' activity. Treatment of sensitive carcinoma cell lines with GW 610 generated co-eluting DNA adducts ( R 2  > 0.7). Time-dependent appearance of γ-H2AX foci revealed subsequent DNA double strand breaks. Propensity for systemic toxicity of benzothiazoles steered development of prodrugs' hydrogels for localised delivery. Clinical applications of targeted therapies include prevention or treatment of recurrent disease after surgical resection of solid tumours. In vitro evaluation of 5F 203 prodrugs' activity demonstrated nanomolar potency against MCF-7 breast and IGROV-1 ovarian carcinoma cell lines.